2022
DOI: 10.3389/fpsyg.2021.797236
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Affective Pedagogical Agents in Multimedia Instruction

Abstract: The goal of the present study is to explore whether the affective states (happy or neutral) of a pedagogical agent (PA) in an online multimedia lesson yields different learning processes and outcomes, and whether the effects of affective PAs depend on the learners’ emotion regulation strategies and their prior knowledge. In three experiments, undergraduates were asked to view a narrated animation about synaptic transmission that included either a happy PA (smiling expression and enthusiastic voice) or a neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 64 publications
0
18
1
1
Order By: Relevance
“…Whereas, for the learners subjected to the high mental load conditions, the enthusiastic human voice increased extraneous cognitive load while decreasing germane cognitive load. Other studies found that while human voices with positive emotional tones such as enthusiasm and happiness in a multimedia learning environment enhanced learning performance, perceived difficulty was not impacted by the voices (Lawson et al, 2021b ; Liew et al, 2017 , 2020 ; Wang et al, 2022 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas, for the learners subjected to the high mental load conditions, the enthusiastic human voice increased extraneous cognitive load while decreasing germane cognitive load. Other studies found that while human voices with positive emotional tones such as enthusiasm and happiness in a multimedia learning environment enhanced learning performance, perceived difficulty was not impacted by the voices (Lawson et al, 2021b ; Liew et al, 2017 , 2020 ; Wang et al, 2022 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Liew et al ( 2017 ) revealed that nonverbal cues, including facial expression, gesture, and voice conveying enthusiasm elevated learners’ positive emotions and intrinsic motivation. Likewise, across three experiments, Wang et al ( 2022 ) found that a pedagogical agent’s positive emotional tone exhibiting a smiling facial expression and an enthusiastic voice evoked higher positive emotions and motivation than a neutral emotional tone displaying a neutral facial expression and a calm voice. From the Cognitive Affective Model of E-learning model perspective, Horovitz and Mayer ( 2021 ) showed that an instructor’s expressed happiness was associated with higher learners’ positive affect (happiness) and motivation.…”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations